”Let Man Remain Dead:” The Posthuman Ecology of Tale of Tales - Sticchi Francesco (Acta Universitatis Sapientiae: Film and Media Studies, 2018)
In this essay I analyse Matteo Garrone’s Tale of Tales (2015) within the perspective of embodied cognition. I consider film experience as an affective-conceptual phenomenon based on the viewer’s embodiment of the visual structures. Baruch Spinoza stands at the foundation of my analytical approach since his thought was based on the absolute parallelism between the body and the mind. This paradigm redefines anthropocentrism and rejects dualism; however, the criticism of the rationalist ideal is also one of the main characteristics of the film Tale of Tales: by staging baroque and excessive characters, it allows the viewer to embody a notion of subjectivity that is performative and relational. Therefore, by combining the cognitive analysis of the film with my theoretical framework I will present a radical criticism of abstract rationality and present an ecological idea of the human.